2021
DOI: 10.1037/aca0000298
|View full text |Cite
|
Sign up to set email alerts
|

Open to laugh: The role of openness to experience in humor production ability.

Abstract: Across two preregistered studies, we addressed the following questions: (1) Does the Big Five personality trait openness to experience predict humor production ability above and beyond intelligence and demographics? (2) Which aspect of openness to experience (intellect vs. openness) predicts humor production ability? In Study 1 (N = 489), participants self-reported on demographics, socioeconomic status (SES), and personality, and were tested on intelligence and humor production. Structural equation modeling sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Studies with these and similar tasks, for example, consistently find that openness to experience has much larger effects on humor production than other traits (e.g., Nusbaum, 2015;Sutu et al, 2020), but tasks that involve non-verbal skill (e.g., delivering jokes vs writing them), public performance, interpersonal charisma, or behavioral disinhibition might reveal larger effects for other traits.…”
Section: Discussionmentioning
confidence: 96%
“…Studies with these and similar tasks, for example, consistently find that openness to experience has much larger effects on humor production than other traits (e.g., Nusbaum, 2015;Sutu et al, 2020), but tasks that involve non-verbal skill (e.g., delivering jokes vs writing them), public performance, interpersonal charisma, or behavioral disinhibition might reveal larger effects for other traits.…”
Section: Discussionmentioning
confidence: 96%
“…Mawang et al (2019) found that male students’ compositions were more creative than that of females in secondary school music students, whereas others (e.g., Barbot & Lubart, 2012; Hassler et al, 1990) found no differences in the creativity of compositions created by male and female composers. Likewise, Sutu et al (2021) found that males were able to generate more humorous responses to an open-ended joke stem, yet Kellner and Benedek (2017) found no significant differences between male and female university students when asked to generate funny captions to cartoons.…”
Section: Gender and Creativitymentioning
confidence: 99%
“…Greengross et al conducted a meta-analysis to examine the sex difference in humor generation and found that men's humor output was rated as funnier than women's, with a combined effect size of 0.321 [18]. Some researchers explored the effect of personality traits on humor generation and found that individuals with high openness to experience have higher verbal skills and are good at appreciating the unconventional features of humor, which is conducive to humor generation [19,20]. In addition, several researchers focused on the impact of individual domain-general ability on humor generation.…”
Section: Empirical Studies Of Humor Generation 121 Behavioral Studies...mentioning
confidence: 99%
“…Simultaneously, by delving into the specific cognitive processing involved in humor generation, a more comprehensive and reliable set of intervention measures for enhancing humor abilities can be formulated. Third, certain individual-level variables, including aspects like humor appreciation, creative skills, and personality, have the potential to impact the psychological processes involved in humor generation [19,20]. Unfortunately, the study has overlooked variability at the individual level.…”
Section: Limitations and Future Researchmentioning
confidence: 99%